Variação espaço-temporal da comunidade arbórea de um fragmento de floresta semidecídua e suas relações com variáveis ambientais, estruturais e ecológicas - Erica Rievrs Borges (2015)
The current study analyzed the tree community dynamics of a 4,0 ha semideciduous forest fragment (known as Mata da Lagoa) in Lavras, MG, Brazil, based on two surveys carried out in the years 2005 and 2011 in 29 20 m x 20 m plots. The main objective was to understand the spatial and temporal variation of the community composition and structure and search for the existence of correlations with ecological, structural and environmental variables. The fragment was at a degrading sylvigenetic phase, indicated by the net decrease in both density and basal area as a result of mortality rates (4,65%.year-1) higher than the recruitment rates (3,10%.year-1) and basal area loss rates (2,94%.year-1) higher than basal area gain rates (2,40%.year-1). This dynamic process, however, showed spatial heterogeneity, since the plots of the Nitosols experienced basal area gain rates (2,85%.year-1) higher than the basal area loss rates (2,72%.year-1). The main causes for this pattern are probably related to soil fertility and past disturbance differences, since the upper parts of the Argisol are closer to the areas more severely impacted by the last disturbance event. The overall linear regression and variation partitioning analyses showed that the dynamic rates were more influenced by past disturbance events, represented by structure and ecological variables, and species composition were more affected by environmental heterogeneity. In general, the dynamic patterns repeated the ones from the last interval (2000 2005), showing a degrading process characterized by a density reduction of the smaller trees and maintenance of the largest individuals. In comparison, Mata da Lagoa is one of the most instable fragments among those studied in the Alto Rio Grande basin, demanding conservation strategies in order to slow down the degradation process.